Influencer Analysis of Prilly Latuconsina’s Online Identity in Building Public Image on Instagram: Analisis Identitas Online Prilly Latuconsina dalam Membangun Citra Publik di Instagram - Amelia, Nike Firnanda Dwi; Nur Fadhilah, Sevia; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
This research aims to analyze Prilly Latuconsina's online identity in building her public image through the Instagram platform. This research uses descriptive qualitative research method by analyzing the content of Prilly's uploads on Instagram, including photos and captions that reflect the values and messages she wants to convey to the audience. The results of this study show that Prilly succeeded in creating a positive and inspiring image through effective visual and narrative communication strategies, reflecting her role as an artist and educator. Erving Goffman's dramaturgy theory is applied to understand how Prilly builds her public image on social media, by distinguishing between the “front stage” and “back stage” in her social interactions. The results of this study provide insight into the importance of personal branding in the context of social media for public figures.